Neonates With In-Utero SSRI Exposure (NeoWISE): a retrospective cohort study examining the effect of newborn feeding method on newborn withdrawal - Cantin, Christina; Li, Wenbin; Snelgrove-Clarke, Erna; Corsi, Daniel; Dennis, Cindy-Lee; Ross-White, Amanda; Brogly, Susan; Gaudet, Laura (International Journal of Population Data Science, 2024)
Introduction Up to 30% of newborns with in-utero selective serotonin reuptake inhibitor (SSRI) exposure experience withdrawal symptoms. The impact of newborn feeding method on alleviating withdrawal has not been investigated. We examined the effect of newborn feeding method (breastfeeding versus formula) among a cohort of Neonates With In-utero SSRI Exposure (NeoWISE). Methods This population-based retrospective cohort study included newborns born in Ontario hospitals between April 1, 2012, and March 31, 2020 to Ontario Drug Benefit Program beneficiaries who filled at least one SSRI prenatal prescription. Linked administrative health and registry data were used. Method of newborn feeding was available from birth to hospital discharge. The primary outcome was newborn withdrawal. The secondary outcome was transfer to the Neonatal Intensive Care Unit (NICU). Adjusted risk ratios (adjRR) in breast- versus formula-fed newborns and our outcomes were estimated using generalized linear models. Propensity scores based on antepartum and intrapartum characteristics and inverse probability of treatment weighting were used to balance differences in maternal-newborn characteristics by treatment. Results Overall, 5,079 newborns were included in the NeoWISE Cohort, with 3,321 (65.4%) exclusively breastfeeding from birth to hospital discharge. Among the breastfed newborns, 50 (1.5%) had neonatal withdrawal versus 41 (2.3%) in the formula-fed newborns. There was no difference in risk of withdrawal in breast versus formula-fed newborns (adjRR 0.86, 95% CI 0.56, 1.34). Breastfed newborns had a reduced risk of transfer to the NICU compared to formula-fed newborns (adjRR 0.80, 95% CI 0.66, 0.97); however, this finding did not persist in sensitivity analysis. Conclusion The rate of newborn withdrawal was low in this cohort of SSRI-exposed neonates and was not associated with feeding method in the hospital. The results of this study inform shared decision-making around newborn feeding for perinatal women who take SSRI medications.